PEER GROUP EDUCATION ON PHBS ABOUT WASTE DISPOSING IN THE GIRLS' DORMITORY - Wiwiek Widiatie (Jurnal Keperawatan Muhammadiyah, 2023)
Objective: Healthy problems are often experienced by students in Islamic boarding schools among others diarrhea, typus, and cholera. This is influenced by the behavior of throwing waste, especially in dormitories, which still need special attention. Peer group education as an effort to improve the behavior of throwing waste in its place. It aims to was to determine the influence of peer group education on PHBS about taking out waste.Methods: The research design used pra eksperiment with one group pretest posttest, a population of 189 santriwati at 4I Ainusyams Ponpes Darul Ulum girls' dormitory, approach purposive sampling technique with the criteria for class XI senior high school students and participated in all activities as many as 34 Santriwatiwati. The instrument of measuring knowledge and attitudes uses questionnaires, while the action are carried out in the way of observation. The analysis is the wilcoxon test (Î±<0.05).Results: Knowledge 0.015, attitude 0.011, and to do 0.000, while the behavior of disposing of waste P value 0.000 (p-value â‰¤ Î±) means that there is an influence of peer group aducation on PHBS's behavior about disposing of waste.Conclusion: This is based on the respondent's desire to improve the degree of health where the peer group education method is considered effectively applied in the dormitory in overcoming problems that occur in the dormitory, especially related to changes in health behavior.